Monetary Policy Rules and Oil Price Shocks - Christian Pierdzioch; Christophe Kamps (Kiel Institute of World Economics (IfW), 2002)
This paper studies the relative performance of alternative monetary policy rules in the presence of oil price shocks in a small open economy optimizing model. Our analysis shows that it is important to distinguish between alternative price indices (CPI, core CPI, and GDP deflator) when modeling the effects of oil price increases. This distinction has important implications for monetary policy as the central bank has to decide which inflation rate to target. Our results demonstrate that targeting the change in the GDP deflator is an inferior monetary policy strategy in the presence of oil price shocks.
Keywords: E32; E52; E58; E31; F41; 330; Monetary policy rules; Open economy; Oil price shocks; Price indices; Geldpolitik; Geldpolitisches Ziel; Kleines-offenes-Land; Dynamische Optimierung; Mineralölpreisschock; Inflation Targeting; Preisindex; Theorie